OPHIOLITES AND ISLAND ARCS IN THE LATE PROTEROZOIC NUBIAN SHIELD - Reischmann, Thomas (Ofioliti, 2000)
The late Proterozoic ophiolites of the Nubian shield can be classified into two groups. One is mainly found in shallow structural positions thrust over presumably older continental crust. The other group predominantly occurs in steep structural orientations within suture zones separating arc terranes. These structural differences reflect the classification of the first group as Tethyan-type and of the second group as Cordilleran-type. The Cordilleran-type ophiolites characterize the ensimatic realm of the Arabian-Nubian shield, whereas the occurrences of the Tethyan-type ophiolites are restricted to the presumed continental margin environment of the Archaean to mid Proterozoic Nile craton. Using the obduction ages of the ophiolites as time markers of ocean closure, the time span of the subduction-related igneous activity and thus the life time of the distinct arc terranes can be estimated to be about 150 Ma.